Pemanfaatan Limbah Cangkang Kerang dan Cangkang Telur pada Beton Geopolimer - Imran, Imran; Attamimi, Aqilah (Politeknik Negeri FakFak, 2024)
Alternative materials are almost always found in the surrounding nature, therefore innovation in the development of concrete mixture composition must continue to be improved. Natural local materials that are prioritized as a substitute for cement have geopolymer material content and contain silica (Si) and alumina (Al) elements. Clam shells are a new phenomenon in several sea sand quarries in Fakfak Regency. If the shell shell waste is not utilized, it will only create useless piles, as is the case with chicken egg shells, even though this waste has the potential to replace lime in making cement. This study aims to determine the characteristics of the material (clam shell waste, chicken egg shells and sand), and to determine the compressive strength produced in variations in the use of 50% LCK + 50% LCTA, 80% LCK + 20% LCTA and 100% LCTA. The results obtained in this study indicate that clam shells can be used as a component of geopolymer concrete because they have basic elements found in geopolymer materials in the form of SiO2, CaO, Al2O3, Al2O3, and MgO. Meanwhile, in chicken egg shells, the dominant element is only CaO. The dominant variation of shellfish shells using a combination of 80% LCK + 20% LCTA variations has the highest compressive strength value compared to other variations of 14.29 MPa at the age of 28 days, while the variation of 100% chicken egg shells only gets a compressive strength result of 2.20 MPa (age 28 days).